Pengaruh manajemen pengetahuan, lingkungan kerja, keterlibatan karyawan, kepemimpinan transformasional dan budaya organisasi terhadap kinerja karyawan melalui kepuasan kerja - Putra, Edy Yulianto; Ariyanto, Hepy Hefri; Maytanius, Jerry (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
Employees are a crucial asset for any business to achieve its goals. The effectiveness and efficiency of employee performance are essential for the success of a business. In other words, the company’s progress depends on the employees’ work results. This research aims to study the impact of knowledge management, work environment, employee engagement, transformational leadership, and organizational culture on employee performance through job satisfaction. The research uses quantitative methods and collects data from 450 respondents through a Google form. The results indicate that employee engagement and work environment do not significantly affect job satisfaction. However, knowledge management, organizational culture, and transformational leadership significantly impact job satisfaction. Organizational culture and transformational leadership do not significantly affect employee performance. In contrast, employee engagement, knowledge management, work environment, and job satisfaction significantly influence employee performance.